Evaluation of Geothermal Prospects in The Patuha Field Based on Derivative Analysis and 3D Inversion of Gravity Anomaly - Dewi, Soraya Tiana; Sarkowi, Muh; Wibowo, Rahmat Catur (EKSPLORIUM, 2025)
The Patuha geothermal field has the potential to be developed as a source of energy for power generation. This study was conducted to evaluate the Patuha geothermal system based on Global Gravity Model Plus Gravity data. The study refers to the Bouguer Anomaly value, which is the difference between the observed gravity value (gobs) and the theoretical gravitational value (gn), or the sum of corrections applied to the gravity measurement. This difference reflects variations in mass density between the survey area and its surroundings, occurring in both lateral and vertical directions. Derivative analysis and 3D inversion of gravity anomalies are used to identify the presence of faults, reservoir prospects, cap rocks, and heat sources. The Complete Bouguer Anomaly map displays decreasing values from southwest to northeast. The high anomaly coincides with Mount Patuha, indicating that this feature may become the heat source. The 3D inversion of the gravity anomaly yielded a density range of 2 g/cm³ to 3 g/cm³. The reservoir prospect is controlled by the graben structure and is located in the Ciwidey Crater. It has a density of 2.5 g/cc, with an area of ​​130 km2, located at a depth of 2200 meters above MSL to 700 meters below MSL. Cap rock crosses along the Cibuni Crater, White Crater, and Ciwidey Crater with a density of 2.66 g/cc at a depth of 2300 meters to 800 meters above MSL. The heat source is shallow and originates from Mount Patuha, with a density of 3 g/cc at a depth of 1500 meters above MSL and 4600 meters below MSL.